The Punishment of God - Phạm, Hong Khương (Khoa Học Công Giáo và Đời Sống, 2022)
People who experience hardship as a result of diseases and natural calamities sometimes ask "why?" and frequently believe that God is punishing them. This essay will shed light on whether God punishes or not. Why does God discipline? What is the Punisher's purpose? These questions are answered to demonstrate that God is good. Evils, both physical and moral, are not God's will. Everyone wants to make others better.